(untitled) (Veterinary Science, 2017)
The echocardiograph parameters correlate with clinical signs, radiographic and electrocardiographic determinations in companion animals. In dogs, the echocardiography is the most indicative complementary test to evaluate size, movement and cardiac architecture. The hypothesis of the study was to evaluate if the acquired mitral valve insufficiency has a positive echocardiography correlation between the left aorta - atrium (Ao/AI) relation and the left aortas - ventricular diameter Ao/VID) with the progress of the disease. The study population consisted in 16 dogs with mitral valve insufficiency without evidence of radiologic cardiac disease. It was found a significant positive correlation between Ao/AI - Ao/VID(r = 0.70; r2 = 0.49; p = 0.003). The results allow affirming that the overload volume that supports the left atrium it was correlated positively with the size of the left ventricular camera and that is proportional with the degree of severity of the cardiac disease.